Comparison between hydroxyapatite and polycaprolactone in inducing osteogenic differentiation and augmenting maxillary bone regeneration in rats - Luchman, Nur Atmaliya; Megat Abdul Wahab, Rohaya; Zainal Ariffin, Shahrul Hisham; Nasruddin, Nurrul Shaqinah; Seng, Fong Lau; Yazid, Farinawati (PeerJ, 2022)
Background: The selection of appropriate scaffold plays an important role in ensuring the success of bone regeneration. The use of scaffolds with different materials and their effect on the osteogenic performance of cells is not well studied and this can affect the selection of suitable scaffolds for transplantation. Hence, this study aimed to investigate the comparative ability of two different synthetic scaffolds, mainly hydroxyapatite (HA) and polycaprolactone (PCL) scaffolds in promoting in vitro and in vivo bone regeneration. Method: In vitro cell viability, morphology, and alkaline phosphatase (ALP) activity of MC3T3-E1 cells on HA and PCL scaffolds were determined in comparison to the accepted model outlined for two-dimensional systems. An in vivo study involving the transplantation of MC3T3-E1 cells with scaffolds into an artificial bone defect of 4 mm length and 1.5 mm depth in the rat’s left maxilla was conducted. Three-dimensional analysis using micro-computed tomography (micro-CT), hematoxylin and eosin (H&E), and immunohistochemistry analyses evaluation were performed after six weeks of transplantation. Results: MC3T3-E1 cells on the HA scaffold showed the highest cell viability. The cell viability on both scaffolds decreased after 14 days of culture, which reflects the dominant occurrence of osteoblast differentiation. An early sign of osteoblast differentiation can be detected on the PCL scaffold. However, cells on the HA scaffold showed more prominent results with intense mineralized nodules and significantly (p < 0.05) high levels of ALP activity with prolonged osteoblast induction. Micro-CT and H&E analyses confirmed the in vitro results with bone formation were significantly (p < 0.05) greater in HA scaffold and was supported by IHC analysis which confirmed stronger expression of osteogenic markers ALP and osteocalcin. Conclusion: Different scaffold materials of HA and PCL might have influenced the bone regeneration ability of MC3T3-E1. Regardless, in vitro and in vivo bone regeneration was better in the HA scaffold which indicates its great potential for application in bone regeneration.